Editorial - Oniwide, Oyetola (NIU Journal of Educational Research, 2025)
This edition of NIU Journal of Educational Research touches on Emotional Regulation, Peer Influence, Parenting Styles, Social Support, Artificial Intelligence in Mechanical Technology, Teachers’ Motivation and Job Effectiveness as well as Sleep Quality and Athletic Performance. One of the papers, in this issue, provides important insights for educators, policymakers, and parents, particularly in socio-economically disadvantaged regions, and underscores the need for a holistic approach to addressing the factors that contribute to academic achievement in secondary education. Another paper also reveals that artificial intelligence in mechanical technology improves learning experience and learning outcome, increases productivity, improves design accuracy, reduces production labour cost, reduces material wastage, saves time and improves environmental health. The paper therefore, recommends that artificial intelligence tools should be incorporated into mechanical technology delivery systems in institutions of learning where mechanical technology is offered and in mechanical technology industries for sustainable development under economic uncertainties in Edo State, Nigeria. On the whole, this edition of NIU Journal of Educational Research features many empirical and theoretical based articles which can be of great benefit to every reader.